Which Dermatological Conditions Present to an Emergency Department in Australia?. (31st March 2014) - Lai-Kwon, Julia; Weiland, Tracey J.; Chong, Alvin H.; Jelinek, George A.
Abstract : Background/Objectives . There is minimal data available on the types of dermatological conditions which present to tertiary emergency departments (ED). We analysed demographic and clinical features of dermatological presentations to an Australian adult ED. Methods . The St. Vincent's Hospital Melbourne (SVHM) ED database was searched for dermatological presentations between 1 January 2009 and 31 December 2011 by keywords and ICD-10 diagnosis codes. The lists were merged, and the ICD-10 codes were grouped into 55 categories for analysis. Demographic and clinical data for these presentations were then analysed. Results . 123 345 people presented to SVHM ED during the 3-year period. 4817 (3.9%) presented for a primarily dermatological complaint. The most common conditions by ICD-10 diagnosis code were cellulitis (n = 1741, 36.1%), allergy with skin involvement (n = 939, 19.5%), boils/furuncles/pilonidal sinuses (n = 526, 11.1%), eczema/dermatitis (n = 274, 5.7%), and varicella zoster infection (n = 161, 3.3%). Conclusion . The burden of dermatological disease presenting to ED is small but not insignificant. This information may assist in designing dermatological curricula for hospital clinicians and specialty training organisations as well as informing the allocation of dermatological resources to ED.